Climate Change Disclosure Impact on Indonesian Corporate Financial Performance - Iriyadi, Iriyadi; Antonio, Yovita (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
This paper aims to observe the impact of climate change disclosure (CCD) towards corporate financial performance (CFP) proxied by returns on assets (ROA), return on sales (ROS), and sales growth. Linear and non-linear approaches are employed for this research. Recommendation from Task Force on Climate-Related Financial Disclosures (TCFD) are applied for content analysis to obtain CCD scores. The target population in this study is 45 best performing companies (LQ45) listed on the Indonesia Stock Exchange (IDX) that disclosed sustainability report from 2014 to 2018. The number of observations is 72 year-companies. The findings show that CCD in large companies decreases ROS and improves ROA, yet in general, the improvement occurs in the long term for ROA and sales growth after a certain level is met (U-curve). In general, providing climate-related information will eventually pay. Financial improvement of the companies has increased despite of low quality of CCD and an indication of positive customer reaction to CCD is noticeable.